Changes in the epidemiology of gastroenteritis in a paediatric short stay unit following the introduction of rotavirus immunisation. Issue 2 (22nd January 2013) - Akikusa, Jonathan D; Hopper, Sandy M; Kelly, Julian J; Kirkwood, Carl D; Buttery, Jim P
<x xml:space="preserve">Abstract</x> Aim Acute gastroenteritis (AGE) has been a significant component of the clinical load in the short stay unit (SSU) at the Royal Children's Hospital (RCH) since its establishment in 2004. Since the introduction of routine rotavirus immunisation in Australia in 2007 there has been a clinical impression of a substantial reduction in AGE managed in the SSU. This study aimed to examine changes in the epidemiology of AGE in the SSU, and RCH overall, between 2005 and 2009 and explore whether this reflects a change specifically in AGE due to rotavirus. Methods Discharge coding data for AGE from all inpatient wards, the SSU and emergency department (ED) at the RCH were examined. Stool virology results for the same period were analysed. Results Since 2007 there has been a 58% reduction in AGE admissions to the SSU. The median age of patients admitted to the RCH with rotaviral enteritis has increased from 1.3 years to 3.8 years. Presentations to the ED for AGE have fallen from 53 to 34 cases per 1000 attendances between 2004 and 2009, and admission rates from the ED have fallen from 23 to 13% of AGE presentations. Detection rates of rotavirus fell from 13.1 to 6.7% between 2005 and 2009. Conclusion A marked decrease in AGE‐related clinical activity and reduction in rotavirus detection at the RCH has occurred since the introduction of routine rotavirus immunisation in Australia. This has significant resource planning implications for units based on short stay models of care.